Analysis of the Relationship between Energy Consumption and Economic Growth in the Commonwealth of Independent States - Syzdykova, Aziza; Azretbergenova, Gulmira; Massadikov, Khairulla; Kalymbetova, Aigul; Sultanov, Darkhan (International Journal of Energy Economics and Policy, 2020)
Since energy is one of the indispensable elements of our lives, it is one of the most studied topics today. Utilization of energy with the highest efficiency capacity is very important for sustaining the growth of the countries. Effects of energy consumption on economic growth differ from country to country depending on economic structure and economic growth process of country. For this reason, there is no exact opinion related to direction of causality relationship between energy consumption and economic growth. In the literature there are four hypotheses (growth, protective, objectivity, feedback) which explain the relationship of the point in the question. In this context, in order to implement a strategically correct energy policy, one of the growth and energy indicators should be tested correctly. This study examines the relationship between energy consumption and economic growth in Commonwealth of Independent States (CIS) for the period of 1992-2018. According to the findings of the study, there is a two-way causality between energy consumption and economic growth in CIS countries. This shows that the feedback hypothesis is valid in these countries. Keywords: Energy Consumption, Economic Growth, CIS countries, Panel Co-integration, Panel Causality JEL Classifications: O40, Q43, Q40 DOI: https://doi.org/10.32479/ijeep.9264